Socialni dialog v poklicnem izobraževanju ali kdo v Sloveniji pozdravlja vajeništvo - Ermenc, Klara S. (Sodobna pedagogika, 2024)
The article explores social partnership and social dialogue in vocational education in Slovenia. Various authors understand social partnership as one of the fundamental guarantees of quality vocational education, as this is not possible without close cooperation between the education sphere and the labour market. In the introduction, it presents the concept of social partnership in Slovenia and sheds light on its development in the post-independence period, places it in a comparative context, and summarizes key evaluations and criticisms of the regulation of this area. The central part of the article is intended to present the results of research on the characteristics and quality of social dialogue in Slovenian vocational education, with an emphasis on apprenticeship. It focuses on the ways of cooperation at the level of programme implementation, where the key partners are schools and companies, partly chambers and trade unions, and emphasizes some aspects of cooperation at the system level, where the main partners are the ministries responsible for education, labour and the economy, which cooperate with the chambers and trade unions. The results show that, despite the examples of good practices, the social partnership does not fully come to life, which is partly the result of the system regulation, which keeps key powers in the school sector, and partly, as it appears, of an underdeveloped social dialogue characterized by an insufficient level of trust between partners and lack of capacity of social partners. Further research will be needed for a deeper insight into the functioning of dialogue, and the current results already have some important implications for the development of vocational education.
Keywords: education; pedagogika; pedagogy; poklicno izobraževanje; Slovenija; socialni dialog; socialno partnerstvo; šolske reforme; vajeništvo; vzgoja in izobraževanje